2001
DOI: 10.1017/s0950268801005933
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the incidence of diarrhoea and prevalence of bacterial pathogens in a cohort of Vietnamese children along the Red River

Abstract: We prospectively studied diarrhoea incidence among 1655 children < 5 years of age in northern Vietnam for 1 year using primarily passive surveillance. Standard culture methods were used to detect bacterial pathogens. Overall 2160 cases occurred (1·3 cases/child per year). Peak rates of diarrhoea occurred in children < 12 months old. Rates ranged from 3·3 cases/child per year in children < 1 year old, to 0·7 cases/child per year in 4-year-olds. Campylobacter, shigella and enterotoxigenic Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 22 publications
3
52
0
1
Order By: Relevance
“…Our study is in accordance with several other studies that reported multiresistance of Shigella to commonly used therapeutic antimicrobials (5,25,26,40). Except for amoxicillin-clavulanic acid (AMC) exhibiting moderate activity to Shigella, other antibiotics were still active against this pathogen.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our study is in accordance with several other studies that reported multiresistance of Shigella to commonly used therapeutic antimicrobials (5,25,26,40). Except for amoxicillin-clavulanic acid (AMC) exhibiting moderate activity to Shigella, other antibiotics were still active against this pathogen.…”
Section: Resultssupporting
confidence: 92%
“…due to limited resources available in the laboratory. Diarrhea was defined as (i) at least three loose (or watery) stools within 24 h, regardless of other gastrointestinal symptoms; (ii) two or more loose stools associated with at least one other symptom of gastrointestinal infection (abdominal pain, cramping, nausea, vomiting, and fever); or (iii) passage of a single loose stool with grossly evident blood and/or mucous (25). Two independent episodes were separated by at least 3 days of being diarrhea-free.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have highlighted the heterogeneous distribution of Shigella serogroups (Pazhani et al, 2005;Taneja et al, 2004). In addition, an increasing number of Shigella isolates have been identified as untypable by serotyping in many countries (Isenbarger et al, 2001;Roy et al, 2006;Zafar et al, 2009). Unusual isolates of S. flexneri were first reported from travellers in Japan with diarrhoea (Matsushita et al, 1992) and from a restaurant-associated outbreak in California (Trevejo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella was also commonly found in our patients, but no typhoidal specimens were isolated. In our sample, E. coli was the least frequent causative agent of acute diarrhea; however, it is more important to the epidemiology of diarrhea in poorer areas [10,11] [12], while it is much more common in other countries [13][14][15].…”
Section: Discussionmentioning
confidence: 99%